Decomposing gender wage gaps: a family economics perspective - Dorothée Averkamp; Christian Bredemeier; Falko Juessen (The Scandinavian Journal of Economics, 2023)
We propose a simple way to embed family-economics arguments for pay differences between genders into standard decomposition techniques. To account appropriately for the role of the family in the determination of wages, one has to compare men and women with similar own characteristics~–~and with similar partners. In US survey data, we find that our extended decomposition explains considerably more of the wage gap than a standard approach, in line with our theory that highlights the role of career prioritization in dual-earner couples.
Keywords: 330; Gender wage gap; wage-gap decomposition; dual-earner households; discrimination